Health, Human Capital, and Life Cycle Labor Supply - Hokayem, Charles; Ziliak, James P. (American Economic Review, 2014)
We use new PSID data on consumption and health, along with information on annual sick time, to estimate a structural labor supply model that incorporates a health capital stock with the traditional human capital learning-by-doing model. The estimates show strong evidence of learning by doing as well as strong persistence in health. However, the estimates reveal that time and money seem to have little effect on health consistent with 'flat of the curve' medicine. We find strong evidence that consumption and leisure are direct substitutes in preferences, and consumption and leisure are each utility complements with good health.